Association of the PPP3CA c.249G>A variant with clinical outcomes of tacrolimus-based therapy in kidney transplant recipients - Salgado PC; Genvigir FDV; Felipe CR; Tedesco-Silva Jr H; Medina-Pestana JO; Doi SQ; Hirata MH; Hirata RDC (Dove Medical Press, 2017)
Patricia C Salgado,1 Fabiana DV Genvigir,1 Claudia R Felipe,2 Helio Tedesco-Silva Jr,2 Jose O Medina-Pestana,2 Sonia Q Doi,3 Mario H Hirata,1 Rosario DC Hirata1 1Department of Clinical and Toxicological Analysis, School of Pharmaceutical Sciences, University of Sao Paulo, 2Division of Nephrology, Hospital do Rim, Federal University of Sao Paulo, Sao Paulo, Brazil; 3School of Medicine, Uniformed Services University of the Health Sciences, Bethesda, MD, USA Background: The effects of genetic variants related to the pharmacodynamic mechanisms of immunosuppressive drugs on their therapeutic efficacy and safety have been poorly explored. This study was performed to investigate the influence of the PPP3CA c.249G>A variant on the clinical outcomes of kidney transplant recipients. Patients and methods: A total of 148 Brazilian patients received tacrolimus (TAC)-based immunosuppressive therapy for 90 days post-kidney transplantation. The PPP3CA rs3730251 (c.249G>A) polymorphism was determined by real-time polymerase chain reaction. Single-nucleotide polymorphism (SNP) data for CYP3A5 rs776746 (CYP3A5*3C; g.6986A>G) were used to eliminate the confounding effects of this variant. Results: The PPP3CA c.249G>A SNP did not influence early TAC exposure, renal function, or other laboratory parameters, including levels of urea, creatinine, glucose, and lipids, and blood counts. This variant also did not account for the cumulative incidence of biopsy-confirmed acute rejection or delayed graft function. Regarding adverse events, PPP3CA c.249A allele carriers initially had a 3.05-fold increased probability of treatment-induced blood and lymphatic system disorders compared with c.249GG genotype individuals (95% confidence interval: 1.10–8.48, p=0.032). However, this result was not maintained after adjusting for body weight and CYP3A5*3C SNP status (p=0.086). Conclusion: The PPP3CA c.249G>A variant does not influence the clinical outcomes of Brazilian patients in the early phase of TAC-based immunosuppressive regimen. Keywords: kidney transplantation, polymorphism, PPP3CA, tacrolimus, adverse events, Brazilian patients